Strategic Factors Affecting Investment Decisions of MNCs - Sarin, Ankit; Arshad, Syed Ali (Indian Journal of Marketing, 2007)
The factors that MNCs study before choosing a particular country for exploration, has undergone extensive research. Still it is felt that there is no exhaustive list of factors, which a corporation must study before choosing a particular market. The present conceptual paper is an attempt to provide a fairly reasonable set of factors which need careful scrutiny before embarking upon cross border operations. The size of the prospective market is perhaps the most important decision as regards investment in an alien market. Closely follows the issue of culture. Needs, that are the basic human requirements, ought to be the same in different countries & cultures but the means of satisfying those needs differ across culture. The availability of skilled & qualified workforce at the local level is a major motivating factor for MNCs.Apart from the tax structure, another factor that attracts FDI to a particular country is the incentives that the country offers to foreign direct investment. The existence of government bodies which regulate the flow & facilitate the process of investment in a particular country are also an important factor. Many of the issues are so intertwined that the study of one automatically leads to study of the other.